Experiential Marketing as a Strategy to Enhance Consumer Engagement in the Local Coffee Industry - Hidayat, Danny; Trianto, Anton; Anggarini, Desy Tri (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the impact of experiential marketing strategies on consumer engagement in the local coffee industry. With a focus on sensory driven experiences, personalized services, and in store events, the research investigates how these strategies influence consumer satisfaction, loyalty, and brand advocacy. Using a mixed methods approach, data was collected through surveys, interviews, and direct observations from multiple local coffee shops. The results indicate that experiential marketing significantly enhances consumer satisfaction and emotional engagement, leading to higher loyalty and positive brand perceptions. Personalized services, in particular, were found to have the greatest impact on customer loyalty. The study concludes that local coffee businesses can leverage experiential marketing to differentiate themselves in a competitive market, fostering long term customer relationships and brand advocacy. Further research could explore the long term effects of these strategies on customer retention and the role of digital tools in enhancing experiential marketing efforts.